2021
DOI: 10.1021/acs.jpcc.1c00529
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Effect of Dopant Ionic Radius on Plasmonic M:ZnO Nanocrystals (M = Al3+, Ga3+, In3+)

Abstract: Understanding the role of dopant deactivation on plasmon frequency and extinction is important for the rational design of plasmonic semiconductor nanocrystals (PSNCs). Aliovalent dopants do not always contribute a free carrier to a localized surface plasmon resonance (LSPR) for many reasons, including the existence of a depletion region, the pinning of carriers at neutral defect sites, or even the formation of a secondary insulating microphase (inclusions) not observable in the powder X-ray diffraction (pXRD).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 58 publications
2
30
0
Order By: Relevance
“…Furthermore, the N e value of TDPA-treated WO 3– x NPLs has a nearly 57% higher in comparison to a Drude approximation of 5.56 × 10 22 cm –3 . This is not surprising because in a recent report on cation-doped zinc oxide NCs, the authors showed nearly 80% difference in N e values between redox titration and Drude model-based calculations . Nevertheless, we predict that this large difference between the experimental and empirical formula-based calculations in N e values of WO 3– x NPLs is due to improper approximation of several parameters: (1) the original Drude model was developed for spherical, NCs where shape factor (κ) is 2.0 (eq ).…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…Furthermore, the N e value of TDPA-treated WO 3– x NPLs has a nearly 57% higher in comparison to a Drude approximation of 5.56 × 10 22 cm –3 . This is not surprising because in a recent report on cation-doped zinc oxide NCs, the authors showed nearly 80% difference in N e values between redox titration and Drude model-based calculations . Nevertheless, we predict that this large difference between the experimental and empirical formula-based calculations in N e values of WO 3– x NPLs is due to improper approximation of several parameters: (1) the original Drude model was developed for spherical, NCs where shape factor (κ) is 2.0 (eq ).…”
Section: Resultsmentioning
confidence: 63%
“…Next, we sought to determine how quantitative is the previously determined N e values, which were calculated using the empirical Drude approximation. To experimentally determine the N e value, we applied a single electron redox titration using nitrosonium tetrafluoroborate (NOBF 4 ) as reported by Strouse and coworkers and others on plasmonic metal oxide and nitride NCs. , A known concentration of NOBF 4 was added to WO 3– x NPL samples (as-synthesized and TDPA-treated) and allowed to react for 15 min before the LSPR spectra were recorded (see the Supporting Information for additional details). All spectra were integrated from 500 to 2500 nm to account for peak broadening and peak shifting to lower energies that are known to occur as free carrier density decreases.…”
Section: Resultsmentioning
confidence: 99%
“…The literature value for the dielectric constant of Cu 5 FeS 4 (3.48) and the frequency-independent Drude model were used for these fits. , Since the effective mass of the carriers in these materials remains largely uncertain, one-electron reductant chemical titrations were performed (Figure A) to independently measure the free carrier density, enabling use of the Drude model to calculate m * for each sample. Determining the free carrier concentration independent of the Drude model is critical toward understanding the properties of plasmonic semiconductors as the Drude model has previously been shown to be inaccurate when calculating the carrier density from the LSPR extinction feature alone. The Drude model- and chemical titration-extracted parameters are listed in Table , while the frequency-independent fits are shown in Figure B.…”
Section: Resultsmentioning
confidence: 99%
“…Results from Sn:In 2 O 3 and M:ZnO (M = Al, Ga, In) show the flaw in ignoring the environment at high carrier concentrations, as site occupation effects lead to charge compensation and deviation from parabolic band theory. 15,16 In these studies, the role of a dampening term (Γ), as described within the Jung and Peterson model, was proposed to account for the deviation and assumed to be dependent on energy-level parabolicity, in analogy to the recently explored InN system. 17 A change in parabolicity will lead to a change in carrier effective mass.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Incorporating a p- or n-type dopant into a semiconductor leads to changes in the Fermi level, often accompanied by perturbation of the electron–electron and electron–phonon interactions for a simple valence band (VB)-conduction band (CB) energy structure. , In such systems, the Drude model will produce a linear trend in LSPR frequency with carrier density as long as vacancies or site occupation changes do not perturb the system. Results from Sn:In 2 O 3 and M:ZnO (M = Al, Ga, In) show the flaw in ignoring the environment at high carrier concentrations, as site occupation effects lead to charge compensation and deviation from parabolic band theory. , In these studies, the role of a dampening term (Γ), as described within the Jung and Peterson model, was proposed to account for the deviation and assumed to be dependent on energy-level parabolicity, in analogy to the recently explored InN system . A change in parabolicity will lead to a change in carrier effective mass.…”
Section: Introductionmentioning
confidence: 99%